Metodología para la construcción de acometidas e instalación de medidores digitales. - Mejía Molina, José Herminio (2015)
This pilot study aims to present the general guidelines for installing digital meters underground or overhead type connections. The Southern Regional Electricity Company (EERSSA) we have single phase measurement systems, two phase or three phase, the type of meter to be installed will depend on their ability. The size varies according to the load to be taking rush to install the following topology: Every meter shall be installed on a metal board, when the case requires the installation of two or more meters should be considered for installation of a meter board. It should be placed in each of the measurement points grounding it will be made with bare copper conductor wiring; the minimum size to 6 AWG shall be used and connected to a rod 16 Copperweld diameter x 1800 mm length.